Strategi Penggunaan Buku Cerita Bergambar untuk Meningkatkan Kemampuan Membaca Anak Usia 5-6 Tahun Di TK Aisyiyah 7 Mataram Tahun 2019/2020 - Jumratu Sani; Baik Nilawati Astini; Nurhasanah Nurhasanah (Indonesian Journal of Elementary and Childhood Education, 2020)
This study aimed to determine the strategy of using picture story books to improve reading skills of children aged 5-6 years at Kindergarten Aisyiyah 7 Mataram in 2019/2020. This type of was a development research. The subjects of this study were 12 children aged 5-6 years. The indicators studied include: Listening to the story read, mentioning the letters of the letters that are known, recognizing words, reading images and understanding the meaning of images. The data collection method used in this study is the observation method. Data analysis used descriptive qualitative analysis. Children's reading ability can be developed through learning activities using picture story books with steps such as (1) preparing and organizing learning media such as picture story books, (2) introducing learning media such as picture story books, (3) knowing the activities to be carried out with learning media, (4) children sit in groups of 2 people, (5) each group of children chooses 1 picture book to read, (6) children read and display facial expressions according to the story's content in turn. The results of this study indicate that there is an increase in children's reading skills by using a strategy of using picture books. The increase can be seen from the percentage of development I which is 54%, development II which is 72% and in development III which is 89%. In conclusion, that children's reading skills can be developed through a strategy of using picture books.